Measurement of cognitive functions in experts and elite athletes: A meta-analytic review - Scharfen, H.-E.; Memmert, D. (Applied Cognitive Psychology, 2019)
An extraordinary physiological capacity combined with remarkable motor control, perception, and cognitive functioning is crucial for high performance in sports. Tests that assess the physical abilities are already well established. Moreover, a growing area of research evolved in the recent past that is particularly concerned with the basic cognitive functions by means of neurocognitive tests in experts and elite athletes. The aim of this meta-analysis (k = 19) is to quantify differences among experts and nonexperts as well as elite athletes and non-elite athletes. In addition, it aims to assemble and compare previous research and analyze possible differences in cognitive functions depending on age, skill level, and used cognitive tasks. Overall, the mean effect size was small to medium (r = 0.22), indicating superior cognitive functions in experts and elite athletes. The factor of skill definition significantly differentiates the cognition-expertise relationship. In contrast, differences in age groups and cognitive areas appeared but were not significant. Future research should prefer the elite rather than the expert definition and distinguish between high-performance and amateur athletes. Furthermore, the findings suggest that it can be beneficial for coaches and sport clubs to integrate cognitive tests as an additional tool for scouting and for optimizing the athletic development of their players.